About Theater of Animated Forms, in Minas Gerais: interview with Conceição Rosière (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
In 1985, the Minas Gerais Puppet Theater Association (ATEBEMG) was created,responsible for promoting, over the years, important dialogues and projects of its members,among which we can affirm the fundamental presence of the puppeteer Conceição Rosière whocontributes, always, for the longevity and vigor of the Association. As a puppeteer, teacher,researcher and member of ATEBEMG, and considering the global situation caused by Covid-19and the “triggering” and latent theme proposed by Móin-Móin Magazine - The performance ofwomen in the Animation Theater -, I felt instigated to register part of the path taken by ConceiçãoRosière and, to interview her in the virtual modality and, thus, to share with different readers thefemale voice translated in the force of a collective.